LITERATURE REVIEW ON CIVIL LIABILITY FOR E-COMMERCE PLATFORMS AS INTERMEDIARIES IN E-COMMERCE DISPUTES COMPARISON WITH THE EUROPEAN UNION: THE ORETICAL EVOLUTION, REGULATORY FOCUS AND PROBLEMS IN CHINA - Ying Wuling; Hartini Saripan; Anida Mahmood; Li Xiaodan, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
With the rapid development of China's e-commerce economy, e-commerce disputes have surged, putting tremendous pressure on the administrative supervision of e-commerce economy and the judicial mediation of civil disputes. This article aims to review relevant literature, laws, and regulations concerning the civil liability of e-commerce platforms as intermediaries in e-commerce disputes. It compares the Chinese framework with that of the European Union (EU), examining the theoretical evolution, regulatory focus, and prevalent problems within the respective legal frameworks governing these platforms. The article highlights the shortcomings and challenges of current regulations for China's e-commerce platforms and provides suggestions for future legal and policy improvements.